Perlindungan Hukum Bagi Konsumen dalam Praktek Bisnis Pinjaman Online Ilegal - Anak Agung Gede Candra Kusuma; Ni Luh Made Mahendrawati; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2022)
Online loans that are developing in today's society will certainly be very helpful, the problem is when people are involved in illegal online loan transactions which often use unjustified methods of collecting. The purpose of this research is to analyze the regulation of online loan transactions in Indonesia and to discuss forms of legal protection for consumers in illegal online loan transactions. The research method used is a normative research type by examining library materials as primary data and secondary data from books and legal journals. The data collection technique of this research is to record and document. And the data analysis technique is by reviewing books, literature and electronic media related to this research. The results of this research indicate that currently legal protection for people involved in illegal online loan transactions is still lacking, because people find it difficult to distinguish between legal online loan financing institutions and which online loan financing institutions are illegal. In this case, an active role from the OJK is needed to oversee the growth of illegal online loans in the community as regulated in the Financial Services Authority Regulation No. 77 of 2016 concerning the implementation of online-based loan transactions, besides that the protection of people involved in online loan transactions is regulated in Law no. 8 of 2019 concerning consumer protection to prevent arbitrariness by online loans to the public.